ALEX index enables detection of alien macroalgae invasions across habitats within a marine protected area. (March 2018) - Piazzi, L.; Gennaro, P.; Atzori, F.; Cadoni, N.; Cinti, M.F.; Frau, F.; Ceccherelli, G.
Abstract: A modified version of the ALien Biotic IndEX (ALEX) has been recently proposed to evaluate biological invasions in macroalgal assemblages. ALEX was applied in a Marine Protected Area where a recreational-fishing port is present testing the following hypotheses: ALEX increases with the distance from the port, it changes between the two directions off the port and it changes among three different habitats: Cystoseira beds, algal turf and dead matte of the seagrass Posidonia oceanica . A total of 78 native macroalgal taxa and 4 introduced species were found, the Chlorophyta Caulerpa cylindracea and the Rhodophyta Apoglossum gregarium, Acrothamnion preissii and Womersleyella setacea . All study sites were in high quality status highlighting that the assemblages investigated were at an early stage of NIS invasion. However, ALEX detected different values among conditions and habitats within the MPA, suggesting a local dynamics of NIS spread and different resistance to invasion of the investigated habitats. Highlights: The ALien Biotic IndEX has been proposed to evaluate alien macroalgal invasion. The study evaluated the effectiveness of ALEX to detect early stage of invasion. ALEX was applied in a Marine Protected Area where a port is present. ALEX detected differences among habitats, distances and directions off the port. Results encourage the employment of ALEX in coastal monitoring plans.